Impact of the Internet on the work of digital journalists in Peru - Yezerska, Lyudmyla (2022)
The Internet has revolutionized the way in which journalists work in the newsrooms. The new situation, derived of the incorporation of the new technologies in various areas of the journalistic industry, it has supposed a metamorphosis of the traditional profiles and the emergence of new professional figures. This article reflects on aspects related to the impact of internet in the work of the digital journalists in Peru. For this, we present the results of the survey "The Internet and Peruvian journalist", realized in major national and some regional newspapers, which discover perceptions, concerns and motivations of the journalists that publish in the digital newspapers.